Interpretasi Teori Belajar Perspektif Psikologi Strukturalisme Pada Mahasiswa Abad 21 - Nazala Wahda Izzati; Arbaiyah Yusuf; Nofi Arum Aqilla; Novi Agatha Nur Khamalia (Peneliti.net, 2023)
This article discusses the understanding of the learning theory from the perspective of structuralist psychology in 21st-century students. Structuralism emphasizes the analysis of elements of thought and the relationships between these elements. In the context of learning, material is broken down into smaller elements and understanding the relationships between these elements is crucial. Self-awareness and introspection play a role in adapting learning approaches. The analysis of consciousness and subjective experiences influences learning strategies. Understanding this theory is important for optimizing students' learning potential and enhancing their achievements and personal development in the modern era.